Pengaruh Fluktuasi Suhu Penyimpanan Beku terhadap Perubahan Mutu Pre-baked Kroisan dan Produk Akhir - Kelvin Muhammad Akbar; Nugraha Edhi Suyatma; Budi Nurtama (Jurnal Mutu Pangan : Indonesian Journal of Food Quality, 2025)
Frozen pre-baked products are widely used in the bakery industry as they enhance productivity, ensure product availability, and expand distribution networks. One of the pastry products that incorporates pre-baked dough is the croissant. However, in practice, frozen storage facilities often experience temperature fluctuations, which can affect the quality of both pre-baked products and their final baked forms. Storage under unstable temperature conditions tends to cause greater product deterioration compared to storage at stable temperatures. This study aimed to compare the quality changes in pre-baked croissants (PBCr) and their final baked products due to temperature fluctuations during PBCr frozen storage. The research was conducted in a bakery industry setting (PT XYZ) by observing product characteristics after freezing (PBCr) and after baking. The observed parameters included weight, volume, and color intensity. Storage under fluctuating temperature conditions led to a significant decline in product quality (p<0.05) in terms of both weight and volume for both PBCr and the final baked products. Conversely, in stable frozen storage conditions, quality deterioration occurred but was not statistically significant. The weight of PBCr showed a significant reduction ranging from -5.7 to -6.5%, while the weight of the final baked products decreased by -15.2 to -18.9%. Volume analysis showed varied results, with both increases and decreases in the volume of PBCr and the final products during storage. Meanwhile, the color intensity of the final products did not show significant differences between PBCr stored under stable and fluctuating temperature conditions.